Conceptual deployment models to secure cloud computing / Hajar Ziglari - Ziglari, Hajar (2012)
Cloud computing is a choice of raising the capacity or adding extra capabilities with no new infrastructure investment to train new personnel, or get licence for new software. Cloud computing is growing fast in the IT industry, but while more information from the individuals and companies are stored in cloud, concerns are growing about safety. Security is the main issue which decreases the cloud growth and complications with data availability, data migration, data integrity and confidentiality continue to plague the market. Objectives contain identifying data security attributes and threats for cloud, discovering some strategies to recover the cloud computing service delivery to business performance and customers and developing a new model to cover some security issues. Deployment models will be analyzed to address users' security concerns with cloud computing based on inter-cloud interaction and with multiple clouds to cooperate. The result was evaluated by three experts named Bharat Tank, Colin Frankham and Dr. Ekatarina Yadova to see the effectiveness of the models. The next step will be about development and corresponding interfaces and design patterns for applications to fit the deployment models and working on security protocols and algorithms in the proposed models to have security support in the cryptography part.